Patient and site characteristics associated with pirfenidone and nintedanib use in the United States; an analysis of idiopathic pulmonary fibrosis patients enrolled in the Pulmonary Fibrosis Foundation Patient Registry - Colin H. Holtze; Elizabeth A. Freiheit; Susan L. Limb; John L. Stauffer; Karina Raimundo; Wayne T. Pan; Kevin R. Flaherty; Hyun J. Kim (Respiratory Research, 2020)
Abstract Background Pragmatic use of the anti-fibrotic medications pirfenidone and nintedanib for idiopathic pulmonary fibrosis (IPF) in the United States (US) has not been studied and may be different from international settings due to structural differences between health care systems. This study examined the relationship between patient- and site-level characteristics and anti-fibrotic (a) use and (b) selection. Methods Data from the Pulmonary Fibrosis Foundation Patient Registry was used to perform univariable and multivariable regressions with generalized linear mixed models. A random effects model examined registry site variation. Results 703 of 1218 (57.7%) patients were taking a single anti-fibrotic of which 312 (44.4%) were taking nintedanib and 391 (55.6%) were taking pirfenidone. Up to 25% of patients using an anti-fibrotic may have been excluded from clinical trial participation due to having too severe disease as measured by diffusion limitation for carbon monoxide. Age (OR = 0.974, p = 0.0086) and diffusion capacity of the lungs for carbon monoxide (per 10% increase in percent-predicted; OR = 0.896, p = 0.0007) was negatively associated with anti-fibrotic use while time (in log of days) since diagnosis (OR = 1.138, p < 0.0001), recent patient clinical trial participation (OR = 1.569, p = 0.0433) and oxygen use (OR = 1.604, p = 0.0027) was positively associated with anti-fibrotic use. Time (log of days) since diagnosis (OR = 1.075, p = 0.0477), history of coronary artery disease (OR = 1.796, p = 0.0030), presence of pulmonary hypertension (OR = 2.139, p = 0.0376), patient clinical trial participation in the prior 12 months (OR = 2.485, p = 0.0002), diffusion capacity of the lungs for carbon monoxide (per 10% increase in percent-predicted; OR = 1.138, p = 0.0184), anticoagulant use (OR = 2.507, p = 0.0028), and enrollment at a registry site in the Midwest region (OR = 1.600, p = 0.0446) were associated with pirfenidone use. Anti-fibrotic use varied by registry site. Rates of discontinuation were modest and nearly identical for the two medications with side effects being the most common reason given for discontinuation. Twenty-three percent (23%, 274) of persons with IPF were using or had recently used an immunomodulatory agent. Conclusions This analysis provides a detailed characterization of IPF treatment patterns in the US; many users of anti-fibrotic medications may not have qualified for inclusion in clinical trials. More research is needed to understand variations in medical decision-making for use and selection of anti-fibrotic medication.